Does Social Transformation Drive Out-Migration? Perceptions and Changes - Setrana, M.B.; Teye, J.K.; Nikoi, E.G.A.; Asiedu, E.; Osei-Amponsah, C.; Yakass, E. (Social Sciences, 2025)
Migration and social transformation are major drivers of socio-economic development. Yet, the linkages between social transformation and migration in Ghana are poorly understood. This article seeks to shed light on how social transformation affects or is affected by migration, using mixed methods with transformationalist and social change theoretical lenses. At the same time, there have been retrogressive transformations in the economic conditions, technology and demography have improved and increased, respectively, and political and cultural factors have remained relatively the same over the past decade. Although there is a perceived bi-directional relationship between social transformation and migration, social transformation exerts greater influence on migration than migration has on social transformation except for higher educational attainment and improved household income. Therefore, the relationship between social transformation and migration is not balanced in our study area as the former influences more than the latter.
Research Article
Keywords: migration; social transformation; globalisation; networks; remittances